Electronic monitoring devices: necessary steps for their successful integration with current asthma care - Howard, Sam (2017)
Health monitoring devices are changing the way we treat, manage and understand chronic health conditions by continuously collecting data about medication use, symptoms, vital signs and a patient’s surrounding environment.